Influence of Different Energy Supply Methods on Performance of Ablative Pulsed Plasma Thrusters - Zhang, Rui; Xi, Wenxiong; Huang, Qiang (Frontiers in Energy Research, 2021)
For a certain configuration of ablative pulsed plasma thruster, changing the initial energy is an effective way to optimize the performance of the thruster. Different energy change methods, will not only affect the macro discharge characteristics and system performance of the thruster but also affect the micro characteristics of the plasma in the discharge channel, equivalent parameters of the discharge circuit, energy conversion efficiency, and so on. But, the internal mechanism of the influence of different initial energy and energy supply methods on the performance of the ablative pulsed plasma thruster is still unclear. In this study, the discharge characteristics, ablation characteristics, and plasma motion characteristics of the thruster with different initial voltage, different capacitance, and different capacitance and voltage configurations at the same energy level were analyzed experimentally and theoretically. These results showed that using the method of increasing the capacitance to increase the initial energy of the system under the same voltage, adopting the power supply method of low voltage and large capacitance under the same initial energy, can effectively increase the impulse generated by the Lorentz force and its proportion in the impulse bit, and increase the proportion of the ablative propellant that is effective ionized and accelerated by Lorentz force, so that the thruster has higher specific impulse and efficiency.